2018
DOI: 10.4103/nmj.nmj_101_18
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum sequelae of the hypertensive diseases of pregnancy: A pilot study

Abstract: Background: Hypertensive disorders are one of the most common medical conditions that may complicate pregnancy. Postpartum blood pressure (BP) pattern is, however, less clear in affected women and decision to discharge them is usually decided arbitrarily. Materials and Methods: A cohort study conducted at Lagos University Teaching Hospital, Lagos, Nigeria, aimed at determining the proportion of pregnant women with pregnancy-induced hypertension (PIH) and preeclampsia (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…22,25 High levels of serum creatinine were associated with persisting hypertension at twelve weeks postpartum among preeclampsia patients (aRR=1.35, 95% CI:1.241-3.606, p=0.032) at this hospital. This result was consistent with the one of Ndayambagye et al 4 in Mulago hospital in Uganda, Saini et al in India 26 as well as that by Babah et al 21 in Nigeria. Because raised serum creatinine is a known marker for chronic renal disease, it is possible that the women who had elevated serum creatinine had underlying kidney injury resulting from either the preeclampsia itself, or probably were previously undiagnosed asymptomatic patients of kidney disease, which per se is an independent predictor of the development and progression of persisting hypertension and its associated morbidity and mortality.…”
Section: Discussionsupporting
confidence: 91%
“…22,25 High levels of serum creatinine were associated with persisting hypertension at twelve weeks postpartum among preeclampsia patients (aRR=1.35, 95% CI:1.241-3.606, p=0.032) at this hospital. This result was consistent with the one of Ndayambagye et al 4 in Mulago hospital in Uganda, Saini et al in India 26 as well as that by Babah et al 21 in Nigeria. Because raised serum creatinine is a known marker for chronic renal disease, it is possible that the women who had elevated serum creatinine had underlying kidney injury resulting from either the preeclampsia itself, or probably were previously undiagnosed asymptomatic patients of kidney disease, which per se is an independent predictor of the development and progression of persisting hypertension and its associated morbidity and mortality.…”
Section: Discussionsupporting
confidence: 91%
“…An elevated serum creatinine level at admission was the only factor associated with persistent hypertension at 3 months after delivery in adjusted models, which is similar to what was found in other studies. 15 , 23 , 27 This could be due to endothelin, a potent endogenous vasoconstrictor peptide produced by endothelial cells, which may result in endothelial dysfunction. Persistently elevated endothelin levels are associated with diminished creatinine clearance.…”
Section: Resultsmentioning
confidence: 99%
“…This information was obtained using an interviewer-administered questionnaire during participant enrollment and a second questionnaire administered 3 months after delivery. Moreover, we performed the following laboratory tests with the following limits of normal set a priori: serum creatinine level (≤106.08 µmol/L [≤1.2 mg/dL]), 23 triglyceride level (2.48 mmol/L), total cholesterol level (5.89 mmol/L), low-density lipoprotein level (3.62 mmol/L), and high-density lipoprotein (HDL) level (0.91 mmol/L). 24 …”
Section: Methodsmentioning
confidence: 99%
“…32 There is an overlooked window period that makes women vulnerable to cardiovascular disease if they do not receive prompt intervention or long-term surveillance following the puerperium phase. This has become alarming because this population is still at higher risk for hypertension in prehypertensive patients 33 and other cardiovascular diseases. 8 A pilot study of postpartum sequelae of the HDP concluded that a tenth of pregnant women with the hypertensive disease had persistent hypertension six weeks after delivery, whereas a high proportion of hypertensive and normotensive pregnant women had blood pressure levels within prehypertensive ranges by six weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…8 A pilot study of postpartum sequelae of the HDP concluded that a tenth of pregnant women with the hypertensive disease had persistent hypertension six weeks after delivery, whereas a high proportion of hypertensive and normotensive pregnant women had blood pressure levels within prehypertensive ranges by six weeks postpartum. 33 Thus, it is crucial to reconsider the extension of the monitoring and follow-up period for patients, especially those with HDP.…”
Section: Discussionmentioning
confidence: 99%